2023
DOI: 10.3390/ma16041366
|View full text |Cite
|
Sign up to set email alerts
|

Soft Actor–Critic-Driven Adaptive Focusing under Obstacles

Abstract: Electromagnetic (EM) waves that bypass obstacles to achieve focus at arbitrary positions are of immense significance to communication and radar technologies. Small-sized and low-cost metasurfaces enable the accomplishment of this function. However, the magnitude-phase characteristics are challenging to analyze when there are obstacles between the metasurface and the EM wave. In this study, we creatively combined the deep reinforcement learning algorithm soft actor–critic (SAC) with a reconfigurable metasurface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…E lectromagnetic (EM) metamaterial is an artificial composite composed of ordered or disordered subwavelength unit structures, with unique EM properties that natural materials do not have [1][2][3][4][5][6][7][8]. By varying the geometry of the artificial resonator, the metamaterial can exhibit characteristics such as the negative refractive index [9,10], backward Cherenkov radiation [11,12], inverse Doppler effect [13][14][15], and plate focusing [16][17][18][19]. In 2008, Landy et al first proposed the concept of metamaterial perfect absorber (MPA) [20], which showed a very high absorption rate but was very thin, and can achieve impedance matching through flexible structural design and structural parameters adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…E lectromagnetic (EM) metamaterial is an artificial composite composed of ordered or disordered subwavelength unit structures, with unique EM properties that natural materials do not have [1][2][3][4][5][6][7][8]. By varying the geometry of the artificial resonator, the metamaterial can exhibit characteristics such as the negative refractive index [9,10], backward Cherenkov radiation [11,12], inverse Doppler effect [13][14][15], and plate focusing [16][17][18][19]. In 2008, Landy et al first proposed the concept of metamaterial perfect absorber (MPA) [20], which showed a very high absorption rate but was very thin, and can achieve impedance matching through flexible structural design and structural parameters adjustment.…”
Section: Introductionmentioning
confidence: 99%